2006
DOI: 10.1111/j.1365-2036.2006.03047.x
|View full text |Cite
|
Sign up to set email alerts
|

Liver injury in long‐term methotrexate treatment in psoriasis is relatively infrequent

Abstract: SUMMARY BackgroundMethotrexate-induced liver damage in psoriasis has led to dermatologic guidelines that stipulate monitoring of liver injury by means of serial liver biopsies. Recent literature data suggest that methotrexate may be considerably less hepatotoxic than previously assumed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
1
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 18 publications
4
65
1
8
Order By: Relevance
“…Caution should be used when placing obese patients on a regimen of methotrexate since these individuals are at greater risk of developing hepatotoxicity compared to non-obese patients (Table IX). [28][29][30][31][32][33][34][35] Caution should also be exercised when using cyclosporine in obese individuals, since serum trough levels of the drug are paradoxically high in this group, increasing the risk of nephrotoxicity (Table X). 36,37 DISCUSSION Obesity and psoriasis: association studies The question of which comes first, psoriasis or obesity, is a common question.…”
Section: Evidencementioning
confidence: 99%
“…Caution should be used when placing obese patients on a regimen of methotrexate since these individuals are at greater risk of developing hepatotoxicity compared to non-obese patients (Table IX). [28][29][30][31][32][33][34][35] Caution should also be exercised when using cyclosporine in obese individuals, since serum trough levels of the drug are paradoxically high in this group, increasing the risk of nephrotoxicity (Table X). 36,37 DISCUSSION Obesity and psoriasis: association studies The question of which comes first, psoriasis or obesity, is a common question.…”
Section: Evidencementioning
confidence: 99%
“…Several studies have shown that methotrexate-associated hepatic fibrosis and cirrhosis are considerably less aggressive than initially reported. 35,36 Many rheumatologists deem the liver biopsy as unnecessary, particularly in healthy patients. The more stringent dermatology guidelines rest on the assertion that hepatic toxicity is greater in patients with psoriasis than in patients with rheumatoid arthritis.…”
Section: Methotrexate and Hepatotoxicitymentioning
confidence: 99%
“…198,199 In obese patients, systemic methotrexate therapy is associated with a higher risk of hepatotoxicity. [200][201][202] Drug-induced weight gain is also a significant side effect of many medications commonly prescribed by dermatologists. Such weight gain can lead to patient noncompliance as well as exacerbation of comorbid conditions related to obesity.…”
Section: Obesity and Dermatologic Pharmacologymentioning
confidence: 99%